Routine magnetoencephalography in memory clinic patients: A machine learning approach. Issue 1 (18th September 2021) - Gouw, Alida A.; Hillebrand, Arjan; Schoonhoven, Deborah N.; Demuru, Matteo; Ris, Peterjan; Scheltens, Philip; Stam, Cornelis J.
Abstract: Introduction: We report the routine application of magnetoencephalography (MEG) in a memory clinic, and its value in the discrimination of patients with Alzheimer's disease (AD) dementia from controls. Methods: Three hundred sixty‐six patients visiting our memory clinic underwent MEG recording. Source‐reconstructed MEG data were visually assessed and evaluated in the context of clinical findings and other diagnostic markers. We analyzed the diagnostic accuracy of MEG spectral measures in the discrimination of individual AD dementia patients (n = 40) from subjective cognitive decline (SCD) patients (n = 40) using random forest models. Results: Best discrimination was obtained using a combination of relative theta and delta power (accuracy 0.846, sensitivity 0.855, specificity 0.837). The results were validated in an independent cohort. Hippocampal and thalamic regions, besides temporal‐occipital lobes, contributed considerably to the model. Discussion: MEG has been implemented successfully in the workup of memory clinic patients and has value in diagnostic decision‐making.